PHYSIOTHERAPY MANAGEMENT FOR DEGENRATION KNEE OSTEOARTHRITIS BILATERAL - Sunyiwara, Arum Sekar; Rahayu, Umi Budi (Academic Physiotherapy Conference Proceeding, 2021)
Intoduction: Osteoarthritis is a degenerative disease characterized by the deterioration of joint cartilage which causes bones to rub against each other and triggers pain, stiffness and movement disorders. Osteoarthritis comes from the Greek word osteo which means bone. arthro which means joint, itis which means inflammation. Case Presentation : A 87 years old patient with Knee osteoarthritis come to PFDA Pekalongan Clinic. The patient had pain in both knees since 1 year ago. The patient feels pain in the knee when sitting to standing position, the patient complains of aches and pains in both knees when walking long distances. Pain is felt during activity. The intensity of pain increases at night. The patient has been to the doctor and has been injected 4 times. Management and Outcome : IR, TENS and strengthening exercises using theraband with hip extension standing position with elastic band and knee extension sitting position with elastic band was performed for 30 minutes per session, 3 times a week for 4 weeks. Before the intervention, the patient still felt pain and impaired functional activities with a NRS value of 6 and a WOMAC score of 28 . However, after a 4-week intervention, there was a decrease in pain (NRS) to 2 and functional disability increased with a WOMAC score of 23. Discussion : Exercise is carried out repeatedly according to a predetermined dose, This is where there is a decrease in subchondral inflammation resulting in decreased pain, and increased stability. To increase functional activity, theraband exercise provides direct stimulation to the skin receptors and which affects proprioception and maximizes sensation around the knee joint thereby increasing the performance of daily activities Conclusion : It can be concluded that in this case, the provision of a physiotherapy intervention program in the form of: IR, TENS and Theraband Exercises performed 3 times a week for 4 weeks was able to reduce pain, increase muscle strength and increase functional activity.